51st AIAA/SAE/ASEE Joint Propulsion Conference 2015
DOI: 10.2514/6.2015-3919
|View full text |Cite
|
Sign up to set email alerts
|

Near-Surface Plasma Characterization of the 12.5-kW NASA TDU1 Hall Thruster

Abstract: To advance the state-of-the-art in Hall thruster technology, NASA is developing a 12.5-kW, high-specific-impulse, high-throughput thruster for the Solar Electric Propulsion Technology Demonstration Mission. In order to meet the demanding lifetime requirements of potential missions such as the Asteroid Redirect Robotic Mission, magnetic shielding was incorporated into the thruster design. Two units of the resulting thruster, called the Hall Effect Rocket with Magnetic Shielding (HERMeS), were fabricated and are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…6 Figure 1 shows a diagram of the testing on the HERMeS TDUs thus far as well as tests that are planned. Testing on the TDU1 included the propellant uniformity test, 7 magnetic shielding characterization test, 8 performance characterization test, [9][10][11] thermal characterization test, 12,13 facility effect characterization test, 9,11,14 and the first wear test campaign. The performance, thermal, and facility effect characterization tests were performed with a single test setup.…”
Section: Introductionmentioning
confidence: 99%
“…6 Figure 1 shows a diagram of the testing on the HERMeS TDUs thus far as well as tests that are planned. Testing on the TDU1 included the propellant uniformity test, 7 magnetic shielding characterization test, 8 performance characterization test, [9][10][11] thermal characterization test, 12,13 facility effect characterization test, 9,11,14 and the first wear test campaign. The performance, thermal, and facility effect characterization tests were performed with a single test setup.…”
Section: Introductionmentioning
confidence: 99%
“…The thruster's magnetic shielding was confirmed using Langmuir probes embedded in the discharge channel walls; a plasma potential of 800 V was measured along the entire length of the inner and outer discharge channel walls. 14 The magnetic shielding test on TDU-1 verified that channel erosion was no longer expected to limit the life of the thruster. Pressure effects testing on the TDU-1 thruster found that the thruster performance was mostly invariant to increased facility background pressure.…”
Section: Introductionmentioning
confidence: 95%
“…This was validated by the plasma wall probe test and wear tests that indicated no measureable erosion on the discharge channel. [27] During the plasma wall probe test campaign, anode potentials were measured at the downstream chamfer edge of the discharge channel, this indicated that the thruster was magnetically shielded. However, while the HERMeS TDU-1 and TDU-3 thrusters wear test campaigns found that discharge channel erosion rates were undetectable, erosion of the front pole covers was observed at measureable levels with high sputter resistant material rendering the front pole covers as the next life-limiting mechanism.…”
Section: Motivationmentioning
confidence: 99%